The role of povidone-iodine versus saline irrigation in preventing surgical site infections in high body mass index patients: a systematic review and meta-analysis - de Albuquerque Farias Camarotti, Thiago; Zecchin Ferrara, Victoria; Ritter Maldaner, Vitória; Graziani e Sousa, Augusto; Prajiante Bertolino, Enrico; Camarotti, Maria; Averbach, Marcelo (International Journal of Infection Control, 2025)
Background: Surgical site infections (SSIs) are common complications post-surgery, associated with increased morbidity, healthcare costs, and prolonged recovery. High body mass index (BMI) patients face an elevated risk due to impaired wound healing and systemic inflammation. Wound irrigation with Polyvinylpyrrolidone Iodine (PVP-I) or normal saline (NS) is commonly used, but their comparative effectiveness in high-BMI patients remains unclear. Objective: The study aims to evaluate whether PVP-I is more effective than NS in reducing SSIs in high-BMI surgical patients. Design: Systematic review and meta-analysis. Methods: PubMed, Embase, and Cochrane databases were searched up to December 2024 for randomized controlled trials (RCTs) and observational studies comparing PVP-I and NS for SSI prevention in high-BMI patients. Risk of bias was assessed using ROB 2 for RCTs and ROBINS-I for non-randomized studies. Odds ratios (OR) with 95% confidence intervals (CI) were pooled using a random-effects model in R Studio 4.4.2. Results: Four studies with 604 high-BMI patients were included. The pooled analysis showed a decreased SSI rate in the PVP-I group, though not statistically significant (OR 0.58; 95% CI 0.29–1.13; P = 0.11; I² = 39.4%). Sensitivity analyses confirmed the robustness of findings. Discussion: The effectiveness of PVP-I may depend on factors like surgery type and the patient’s clinical status. Although irrigation may have a protective effect, effective preventive strategies should consider the antiseptic agent and perioperative patient optimization. Conclusion: This meta-analysis suggests that PVP-I irrigation may reduce SSIs in high-BMI patients, though statistical significance was not reached. Further research is needed to confirm its potential benefits.